2017
DOI: 10.1038/srep42220
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol tailors cell adhesivity of RGD displaying surfaces: multicomponent models monitored optically

Abstract: The interaction of the anti-adhesive coating, poly(L-lysine)-graft-poly(ethylene glycol) (PLL-g-PEG) and its Arg-Gly-Asp (RGD) functionalized form, PLL-g-PEG-RGD, with the green tea polyphenol, epigallocatechin-gallate (EGCg) was in situ monitored. After, the kinetics of cellular adhesion on the EGCg exposed coatings were recorded in real-time. The employed plate-based waveguide biosensor is applicable to monitor small molecule binding and sensitive to sub-nanometer scale changes in cell membrane position and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(121 citation statements)
references
References 66 publications
1
119
0
Order By: Relevance
“…Several studies have shown that EGCG can bind to laminin (Peter et al, 2017;Suzuki and Isemura, 2001) and disturb the adhesion of cells to the extracellular matrix (Bracke et al, 1987;Chen et al, 2003;Suzuki and Isemura, 2001) finally leading to an altered cell migration pattern (Bal-Price et al, 2017;Barenys et al, 2017a;Nyffeler et al, 2017). The structural moieties inducing this altered cell migration seemed to be galloyl/pyrogallol groups because in a previous study, catechins lacking these residues did not disrupt cell adhesion (Barenys et al, 2017a).…”
Section: Egcg ≈ G37 > M2 > M1 ≈ G56 > Nano-egcgmentioning
confidence: 90%
“…Several studies have shown that EGCG can bind to laminin (Peter et al, 2017;Suzuki and Isemura, 2001) and disturb the adhesion of cells to the extracellular matrix (Bracke et al, 1987;Chen et al, 2003;Suzuki and Isemura, 2001) finally leading to an altered cell migration pattern (Bal-Price et al, 2017;Barenys et al, 2017a;Nyffeler et al, 2017). The structural moieties inducing this altered cell migration seemed to be galloyl/pyrogallol groups because in a previous study, catechins lacking these residues did not disrupt cell adhesion (Barenys et al, 2017a).…”
Section: Egcg ≈ G37 > M2 > M1 ≈ G56 > Nano-egcgmentioning
confidence: 90%
“…EGCGs can be adsorbed onto the polymeric layer of poly(l‐lysine)‐graft‐PEGs functionalized with Arg‐Gly‐Asp (RGD sequences for cell adhesion) via hydrogen bonds . The binding affinity of oxidized EGCGs is higher than that of nonoxidized EGCGs.…”
Section: Surface Engineering Strategies Using Pyrogallol Materialsmentioning
confidence: 99%
“…problem not yet solved. However, they have clear advantages when the biomolecular adsorption, prior to the adhesion of living cells, has to be also recorded in a single experiment [55].…”
Section: Molecular Force Sensors [50] Inside Cells Based On Förster Rmentioning
confidence: 99%